Alfabetização científica e tecnológica em contexto de sociedade de risco : diálogos e possibilidades para um ensino de química voltado á formação cidadã - Amaral, Luana Carla Zanelato do (2022)
The study starts from the premise that the Chemystery teaching offered in basic education is unsatisfactory, mainly in terms of its contribution to the humanistic development of students, revealed by their active and conscious participation in events present in society.This new look at the Chemistry teaching was identified, in the present investigation, with the process of Scientific and Technological Literacy (ACT) from the perspective of the Belgian Philosopher Gérard Fourez, in addition to Ulrich Beck's discussions on Risk Society. The problem announced in the study is linked to the teaching model observed in the educational system, which privileges the accumulation of content aimed at school tests and exams, favoring the students to understand and interact in and with society. Such a crisis that settles in teaching has opened space for the discussion of didactic proposals in the field of scientific education and that are aimed at bringing to the classroom a science aimed at discussing economic, political, social and humanistic aspects, as announced by Fourez. (1997). Guided by these theoretical discussions, a didactic sequence was prepared aimed at promoting citizen education, covering the topic of Pesticides, focusing on the content of organic functions and solubility of organic compounds. The study is guided by the following question: What are the contributions of a teaching proposal that articulates the ACT with the Risk Society discussions in the quest to promote a citizen education to high school students? The main objective of the investigation is to analyze in the voice of teachers who work in basic education, the pertinence of the elaborate didactic sequence. This, in turn, was elaborated based on the assumptions of the ACT, especially focused on the attributes autonomy, mastery and communication, as well as discussions regarding the risks inherent to decision-making in contemporary society. The didactic sequence was structured in eight meetings (16 class periods) and was validated with a group of teachers who work in basic education, through a continuing education course - university extension, held in five meetings (20 hours). The qualitative, descriptive and interpretive research uses three instruments to produce the data, namely: a questionnaire applied to the population under study, a logbook filled in by the researcher after each meeting of the course held and semi-structured interviews with the participants. The results were discussed based on Discursive Textual Analysis and organized into three categories given a priori (Attributes of ACT, Risk Awareness and Citizenship) and two emerging ones (Interdisciplinarity and Fighting Scientific Obscurantism). Such results point to the relevance of the didactic sequence both in terms of theoretical structuring, including inferring an understanding of the expression citizen education from the studied references, and in terms of its operationalization in High School. As a central aspect of the study is the opportunity brought by the didactic sequence to the institution of debate on issues related to science and its importance in life in society.